Asas Keseimbangan Dalam Pembangunan Sistem Hukum Pidana Nasional Berdasarkan Pancasila Menuju Pembaharuan Kitab Undang-Undang Hukum Pidana (KUHP) Nasional - Tabiu, Ramadan; Heryanti, Heryanti; Safiuddin, Sahrina (Halu Oleo University, 2021)
This research discusses the principle of balance in the development of the national criminal law system based on Pancasila towards the renewal of the national criminal code. The National Criminal Law System must be structured or build based on the principle of balance that comes from two pillars, namely the National Legal System section and the National Development section. The National Legal System is oriented to the balance values of Pancasila, namely the values of God (Moral-Religious), Humanistic Values (Humanistic), and Social Values (Nationalistic, democratic and social justice). Meanwhile, the National Development section is oriented towards the balance of development goals that are oriented social defence and social welfare. The two pillars of the development of the National Criminal Law System are in the renewal of the national Criminal Code which underlies the principle of balance in the RKUHP. Some concepts of the principle of balance in the RKUHP are monodualistic balance, balance of legality principle and principle of guilt, balance of formal and material legality principles and balance formal and material wedderechtelijkheid, balance between social defence and social welfare, balance victim and oriented criminal, and the balance of victim protection and individual improvement.